Case Study: Enteral Nutrition in Stroke Patients with Nasogastric Tube at Undata Hospital - Pamolango, Julio Alvero; Pettalolo, Sri Rezeki; Toding, Selly; Nurdiana, Nurdiana; Imansari, Adillah; Anggraini, Anissa (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of this study was to determine the adequacy of commercial enteral nutrition for nutrition needs of stroke patients with Nasogastric Tube (NGT) installation at Undata Hospital. The research was a case study of one stroke patient with NGT. The patient's nutrient intake for three days was measured for energy requirement (87.6%), carbohydrates (76.7%), protein (83.76%), and fat (122.98%). The patient was given commercial food Blendera-MF and Virgin Coconut Oil (VCO) in moderation without incidence of vomiting. Therefore, giving enteral feeding (Blendera-MF) to patients fulfills their nutritional needs.